1997
DOI: 10.1021/bi962335s
|View full text |Cite
|
Sign up to set email alerts
|

Selective Stabilization of Triplex DNA by Anthraquinone Sulfonamide Derivatives

Abstract: A series of cationic anthraquinone derivatives was investigated for their ability to stabilize duplex and triplex DNA. Thermal denaturation experiments demonstrate that each of these compounds stabilizes the [poly(dT) x poly(dA) x poly(dT)] triplex without significantly affecting the [poly(dT) x poly(dA)] duplex. The amount of stabilization is determined by the number and placement of the cationic substituents on the anthraquinone skeleton. The stabilization arises primarily from higher affinity binding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…Sonicated salmon sperm DNA, poly[d(GC)], poly(dT) (all from Amersham Pharmacia), Escherichia coli tRNA (Sigma), a T 4 -hairpin (5Ј-CGCGCGCGTTTTCGCGC-GCG-3Ј), and the sequence d(T 4 G 4 ) in a double-strand (5Ј-CGCGA ATCGCT T T TGGGGTACCCCA A A AGCGAT T-CGCG-3Ј) (all from Microsynth; Balgach, Switzerland) were dissolved in 50 mM Tris͞50 mM NaCl, pH 7.4. Triplex DNA competitor poly(dT)⅐poly(dA)⅐poly(dT) was prepared as described (24). Phosphatidylcholine (100 mg͞ml, Sigma) was dissolved in hexane.…”
Section: Methodsmentioning
confidence: 99%
“…Sonicated salmon sperm DNA, poly[d(GC)], poly(dT) (all from Amersham Pharmacia), Escherichia coli tRNA (Sigma), a T 4 -hairpin (5Ј-CGCGCGCGTTTTCGCGC-GCG-3Ј), and the sequence d(T 4 G 4 ) in a double-strand (5Ј-CGCGA ATCGCT T T TGGGGTACCCCA A A AGCGAT T-CGCG-3Ј) (all from Microsynth; Balgach, Switzerland) were dissolved in 50 mM Tris͞50 mM NaCl, pH 7.4. Triplex DNA competitor poly(dT)⅐poly(dA)⅐poly(dT) was prepared as described (24). Phosphatidylcholine (100 mg͞ml, Sigma) was dissolved in hexane.…”
Section: Methodsmentioning
confidence: 99%
“…This study revealed that the 1,4 compounds destabilize DNA triplexes, leading to dissociation of the third strand, whereas their 2,6 isomeric analogues bind to and stabilize triple-stranded structures. A related study has also shown that selective stabilization of triplex DNA can be achieved with a series of disubstituted anthraquinone sulfonamides and suggested that 2,7-functionalised compounds are more potent than their 2,6 counterparts [117]. We have also compared the activity of four di-substituted and two monosubstituted amidoanthraquinone compounds, and have examined how the position of the cationic substituents affects triplex affinity [118].…”
Section: Triplex Binding Ligandsmentioning
confidence: 98%
“…It has helped in the design of one of the most efficient triplex stabilizers to date, BQQ, by suggesting that addition of a new ring to the BfPQ molecule would enhance stacking interactions with the Watson strand of the triple helix [126]. A rationale has been provided for the differential effects of 2,6-, 2,7-and 1,4-disubstituted anthraquinone derivatives on triplex stabilization [127,128]. Molecular modelling has also suggested that neomycin displays a good charge and shape complementarity with the Watson-Hoogsteen groove of triplexes [124,129].…”
Section: Structural Featuresmentioning
confidence: 99%